The Crosstalk between Cancer Stem Cells and Microenvironment Is Critical for Solid Tumor Progression: The Significant Contribution of Extracellular Vesicles - Chiara Ciardiello; Alessandra Leone; Alfredo Budillon (Stem Cells International, 2018)
Several evidences nowadays demonstrated the critical role of the microenvironment in regulating cancer stem cells and their involvement in tumor progression. Extracellular vesicles (EVs) are considered as one of the most effective vehicles of information among cells. Accordingly, a number of studies led to the recognition of stem cell-associated EVs as new complexes able to contribute to cell fate determination of either normal or tumor cells. In this review, we aim to highlight an existing bidirectional role of EV-mediated communication—from cancer stem cells to microenvironment and also from microenvironment to cancer stem cells—in the most widespread solid cancers as prostate, breast, lung, and colon tumors.